Forzamiento radiativo directo debido a los aerosoles atmosféricos en Perú utilizando técnicas de sensoramiento remoto - Angeles Vasquez, Roberto Julio (2022)
We describe the results of the study of aerosol optical depth (AOD) and Direct Radiative Forcing (DRF) at the top of the atmosphere (TOA), obtained in the period 2004 using the MODIS sensor of the TERRA satellite for Peru. Where it is observed that the AOD value can take maximum values around 0.5, resulting in aerosol DRF in the upper part of the atmosphere. The results indicate that the FRD is between [-5 0] W / m2.